Pelatihan Pengembangan Media Pembelajaran Menggunakan Aplikasi Canva di Madrasah Ibtidaiyah - Handayani, Tutut; Syarifudin, Ahmad; Tastin, Tastin; Nurlaili, Nurlaili; Bujur, Dian Andesta; Al-Ihwana, Al-Ihwana; Wahyudi, Khoiri; Saputra, Agra Dwi (TAAWUN, 2023)
In the era of globalization, we are faced with erratic changes, like fishermen on the "high seas" who can mislead if they do not have a "compass" as a guide and act to sail it. This has resulted in a non-linear relationship between education and employment. Canva learning, at this stage, observations or observations will be carried out in the field regarding the obstacles experienced by the teacher when carrying out learning in class, especially when teaching the topic of procedure text material. Because what happens in the workforce is difficult for the world of education to follow, this activity method is carried out in community service activities for the Madrasah Ibtidaiyah Teacher Education Study Program (PGMI). They are namely conducting workshops on making learning media to support teaching and learning activities using the Canva application, which is carried out online. Offline at Madrasah Ibtidaiyah, the results of the activities can be concluded, and the teacher understands the development of using the Canva application. The results show that using digital-based media has never been done with several contributing factors—learning trends in the 21st-century demand learning resources that are unlimited in number. As the initial foundation for students to understand knowledge and technology, elementary schools need to instill the importance of using media in both the 2013 curriculum and the Merdeka Learning curriculum, whose aim is to increase interest and results. Learning of students at the Madrasah Ibtidaiyah level.